RE-IMAGINING BIKO - Hook, Derek (PINS-Psychology in Society, 2025)
Mangcu, Xolela (2012) Biko: A biography. Cape Town: Tafelberg. ISBN 978-0-624-05413-9. Pages 348. Xolela Mangcu’s recent biography of Steve Biko takes up its place in the contested field of “Biko Studies”. It remains an open question as to why, given the explosion of scholarly interest in Biko, and his ever-increasing popularity as an icon of the liberation struggle, it has taken this long for a self-declared biography of Biko to appear.